Strategi Fundraising dan Filantropi Pengelolaan Dana di Badan Amil Zakat Nasioal Kabupaten Gresik - bariroh, reza silvi; Mufti labib (Sekolah Tinggi Ekonomi dan Bisnis Islam (STEBIS) Al-Ulum, 2025)
This study aims to analyze fundraising strategies and philanthropic practices in fund management at the National Zakat Agency (BAZNAS) of Gresik Regency. The study employs a qualitative approach with a case study method to deeply understand the processes of collecting and distributing zakat, infak, and sedekah (ZIS) funds. The research findings indicate that BAZNAS Gresik Regency implements two main strategies for fund collection, namely the Ayo Belajar Infak (ABI) Program and the Zakat Program. The ABI Program focuses on education and habituation of infak among students, while the Zakat Program is aimed at communities that have fulfilled the obligatory zakat requirements through professional zakat and zakat on wealth. Furthermore, fund distribution is carried out through five main programs, namely Gresik Cerdas, Gresik Peduli, Gresik Sehat, Gresik Berdaya, and Gresik Taqwa. These five programs reflect BAZNAS's efforts in creating social welfare, economic empowerment, and spiritual enhancement of the community. Overall, the implemented fundraising and philanthropy strategies demonstrate high effectiveness in increasing community participation, strengthening public trust, and supporting transparent, professional, and sustainable ZIS fund management. Keywords: Fundraising, Philanthropy, Zakat, BAZNAS